2020
DOI: 10.1002/jmv.26297
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in IL4RA, IL6, and IL12B genes and susceptibility to hepatitis B and C virus infections among Iraqi patients

Abstract: Hepatitis B and C viruses (HBV and HCV) are common causative pathogens of viral hepatitis. Progression of both infections is determined by virus‐ and host‐related factors. Cytokines are important host genetic factors that may have a predisposing role in HBV and HCV infections. This case‐control study evaluated the genetic association of IL4RA+1902 (rs1801275), IL6−174 (rs1800795), IL6−597 (rs1800797), and IL12B−1188 (rs3212227) variants with chronic HBV and HCV infections among Iraqi patients. A total of 220 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Although the frequency of the IL6-174G/C polymorphism was not identified as associated with HBV infection, or with variations in IL-6 levels and viral load in the present study, the homozygous polymorphic (CC) genotype was associated with reduced risk for the development of HBV infection, while the GG genotype was associated with increased risk among Iraqi patients [ 38 ]. The meta-analysis study performed by Wang et al (2019) showed that the GC genotype represented a risk for hepatitis C. In contrast, in hepatitis B, both the GG genotype and the association of the GG + GC genotype were identified with the risk for the development of the disease [ 39 ].…”
Section: Discussionmentioning
confidence: 84%
“…Although the frequency of the IL6-174G/C polymorphism was not identified as associated with HBV infection, or with variations in IL-6 levels and viral load in the present study, the homozygous polymorphic (CC) genotype was associated with reduced risk for the development of HBV infection, while the GG genotype was associated with increased risk among Iraqi patients [ 38 ]. The meta-analysis study performed by Wang et al (2019) showed that the GC genotype represented a risk for hepatitis C. In contrast, in hepatitis B, both the GG genotype and the association of the GG + GC genotype were identified with the risk for the development of the disease [ 39 ].…”
Section: Discussionmentioning
confidence: 84%
“…The G allele may serve as a risk factor for elevated serum IL-6 levels and progression to macrophagic activation syndrome [ 29 ]. An investigation conducted in Iraq supports the concept that the IL-6 − 597 A > G variant is associated with susceptibility to HBV and HCV infections [ 30 ]. However, a Chinese study found no association between HBV resistance and the − 174G > C and − 597 A > G variants [ 31 ].…”
Section: Discussionmentioning
confidence: 92%
“…Only nine studies reported the role of IL‐12B polymorphism in patients infected with HBV 28–36 29 but this is the first study concerning the association between CHB Tunisian patients and IL‐12B 3′‐UTR 1188 AC polymorphism from different cities of Tunisia.…”
Section: Discussionmentioning
confidence: 95%
“…The discrepancy between this study and the study of Ben Selma and colleagues is that recruited patients and controls of his study may not be representative of the general population. Also, studies conducted in Chinese, 31,35 Iraq, 28 Korean, 33 and Saudian 18 populations found that the CC and AC genotypes of IL‐12B were significantly associated with HBV. The discrepancies between our study and studies conducted in other regions of the world might reflect differences in disease etiology, the underlying molecular mechanisms and/or environmental exposures in different populations.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation